The Influence of Facebook to Satisfy and Engage Football Fans: A Study with The Portuguese Professional Football Clubs in the 2nd League - Sílvia FARIA; Manuel Sousa PEREIRA; Pedro FERREIRA; Paula RODRIGUES (Communications of International Proceedings, 2021)
The growing usage of social media is changing the way brands interact with customers and answer their needs and wants. Marketers are using various means to reinforce their brands’ image and positioning, promoting customers’ satisfaction and engagement. Despite its growing acceptance by companies and customers, there are still some questions related to the extension of social media platforms as marketing tools and their impact on brand awareness, customer satisfaction and a relationship in time.  We want to continue this discussion by focusing on the impact of social media marketing activities on Facebook and football clubs’ brand awareness, promoting fans’ satisfaction and engagement. We seek to understand whether the Facebook pages of the Portuguese 2nd league football teams have an impact on satisfaction and on the quality of the relationship their fans develop with the club. The paper reviews marketing literature on social media, customer satisfaction and engagement. A structured questionnaire was applied to a sample of 272 participants, tested using SPSS Statistics version 24.0 and structure equation model - AMOS 24.0. Despite being limited to two football clubs on the north of the country, with participants restricted to the authors’ networking and the clubs’ supporter’s database, it provides data that support the importance of social networks for any organization, regardless of size and/or business sector, mainly sports clubs. Findings indicate that the majority of initiatives on social media marketing – Facebook-, contribute in a positive way to supporters’ satisfaction and engagement. Portuguese football club managers need to use Facebook as a way to communicate and promote lasting relationships with supporters.
Keywords: Social Media; Facebook; Satisfaction; Engagement.